The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/eat.23260
|View full text |Cite
|
Sign up to set email alerts
|

A framework to conceptualize personal recovery from eating disorders: A systematic review and qualitative meta‐synthesis of perspectives from individuals with lived experience

Abstract: Background: An extensive literature exists describing treatment interventions and recovery from eating disorders (EDs); however, this body of knowledge is largely symptom-based and from a clinical perspective and thus limited in capturing perspectives and values of individuals with lived experience of an ED. In this study, we performed a systematic review to coproduce a conceptual framework for personal recovery from an ED based on primary qualitative data available in published literature. Methods: A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 44 publications
6
60
0
3
Order By: Relevance
“…In this regard, studies have found that people with ED have lower levels of meaning in life than recovered patients (de la Rie et al, 2007), problems with their identity (Stein and Corte, 2007), feelings of hopelessness (Robinson et al, 2015), and poor quality of life (Tomba et al, 2017). In a recent study, Wetzler et al (2020) confirmed that connectedness, hope, and optimism about the future, identity, meaning in life, and empowerment are important components of recovery in ED participants. Thus, patients indicated that they found meaning in their lives from ED, and finding actual meaning in life and important goals and values beyond ED is a very important part of recovery.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, studies have found that people with ED have lower levels of meaning in life than recovered patients (de la Rie et al, 2007), problems with their identity (Stein and Corte, 2007), feelings of hopelessness (Robinson et al, 2015), and poor quality of life (Tomba et al, 2017). In a recent study, Wetzler et al (2020) confirmed that connectedness, hope, and optimism about the future, identity, meaning in life, and empowerment are important components of recovery in ED participants. Thus, patients indicated that they found meaning in their lives from ED, and finding actual meaning in life and important goals and values beyond ED is a very important part of recovery.…”
Section: Discussionmentioning
confidence: 95%
“…One seemingly insurmountable obstacle for effective treatment of AN is the identification of sources of reinforcement that prove more valuable than the drive for thinness. Recovery from AN often necessitates the individual expand their life to include other valued activities, which can be difficult due to how highly the illness itself is valued [ 22 , 23 ]. Supportive relationships have been highlighted as an important factor in recovery [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recovery from AN often necessitates the individual expand their life to include other valued activities, which can be difficult due to how highly the illness itself is valued [ 22 , 23 ]. Supportive relationships have been highlighted as an important factor in recovery [ 23 ]. However, it is unclear whether individuals with AN value friendships and relatedly, whether friendships would be sufficient competition for the disorder during recovery.…”
Section: Introductionmentioning
confidence: 99%
“…de la Rie et al, 2005, Hay, 2003, Latner et al, 2008. Θ ΔΡΤ, όμωσ, φαίνεται να ζχει ςοβαρι επίπτωςθ και ςτθ γενικι υγεία και τισ κοινωνικζσ ςχζςεισ, εφρθμα που επίςθσ είναι αναμενόμενο και ερευνθτικά επιβεβαιωμζνο (Doll et al, 2005, Hay, 2003 , Padierna et al, 2002, Stockford et al, 2019, Wetzler et al, 2020.…”
Section: μετριςεισ εξαμινου και ζτουσ τθσ κεραπείασunclassified
“…Αυτοί οι παράγοντεσ είναι πικανό να ςυνδζονται με τθ διαταραχι, αλλά δεν είναι ςαφζσ εάν αποτελοφν αιτία ι αποτζλεςμα. Ωςτόςο, οι περιςςότερεσ προθγοφμενεσ ζρευνεσ ζχουν προςδιορίςει αυτά τα ελλείμματα ωσ παράγοντεσ κινδφνου για τθν εμφάνιςθ ι διατιρθςθ τθσ ΔΡΤ (Cervera et al, 2003, Fairburn et al, 1999, Haslam et al, 2012, Stockford et al, 2018, Wetzler et al, 2020, Wade et al, 2008.…”
Section: μετριςεισ εξαμινου και ζτουσ τθσ κεραπείασunclassified